Inclusión laboral de las personas con discapacidad en el Gobierno Autónomo Descentralizado provincial de Orellana 2022 - Shiguango Heredia, Aracely Soledad (2024)
This research was developed in the Provincial Decentralized Autonomous Government in Orellana with the objective of analyzing the labor inclusion of people with disabilities, to improve the conditions of opportunities of this vulnerable group. The methodology used to develop the study was descriptive and analytical, which offered a complete vision of labor inclusion, since through the interviews and surveys carried out, a clear vision of the current state and perceptions was obtained, exploring the causes and relationships underlying issues that affect inclusion, which allowed us to design an action plan to create a more accessible and equitable work environment. Among the most relevant results, it can be noted that a large percentage of those surveyed remained neutral in relation to important criteria regarding the recruitment and selection processes, as well as the level of satisfaction regarding permanence and professional development. Consequently, it is important to implement an action plan that creates a more inclusive and accessible work environment that benefits all employees and the organization as a whole and creates new work opportunities for this vulnerable group.